Vadose zone classification and aquifer vulnerability of the Molototsi and Middle Letaba Quaternary Catchments, Limpopo Province, South Africa - Van Wyk, Yazeed (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2013.